CIMA - C02 Fundamentals of Financial Accounting: Study Text - BPP Learning Media (BPP Learning Media, 2012)
The C02 Study Text concentrates on the key areas of the syllabus and takes account of the examiner's guidance on how topics will be assessed. It includes a step-by-step approach to topics that students may find difficult, such as control account reconciliations and suspense accounts. There are lots of examples and questions in each chapter to help you practise the techniques required. There are also quick quizzes in the assessment style at the end of each chapter. In addition, there is a question bank of computer-based assessment style questions at the end of the Study Text.